2016
DOI: 10.1038/mp.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic functional connectivity in late-life depression: trajectories over the course of pharmacotherapy in remitters and non-remitters

Abstract: Previous studies in late-life depression (LLD) have found that patients have altered intrinsic functional connectivity in the dorsal default mode network (DMN) and executive control network (ECN). We aimed to detect connectivity differences across a treatment trial among LLD patients as a function of remission status. LLD patients (N=37) were enrolled into a 12-week trial of venlafaxine and underwent five functional magnetic resonance imaging resting state scans during treatment. Patients had no history of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 74 publications
6
78
0
Order By: Relevance
“…It is supported by results from previous studies about late-life depression (LLD). LLD usually has a hyperactive DMN (increased rumination, defected cognition) and a hypoactive ECN (low cognitive control associated with emotional response), which may reflect clinical features of depressive symptoms (Aizenstein et al, 2014;Karim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is supported by results from previous studies about late-life depression (LLD). LLD usually has a hyperactive DMN (increased rumination, defected cognition) and a hypoactive ECN (low cognitive control associated with emotional response), which may reflect clinical features of depressive symptoms (Aizenstein et al, 2014;Karim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies [Chan et al, ; Wang et al, ], however, support our finding by showing a progressive reduction in the FA with demyelination and a steeper decline when the RT dose was high. In addition, we think that the occurrence of abnormal regional functioning and inter‐regional FC earlier (<12 months) than the white matter damage (>12 months) was reasonable because brain function might be more vulnerable or sensitive to attack [Karim et al, ]. Interestingly, similar white‐matter regions (the periventricular areas) were also found to be frequently targeted in normal aging subjects [Habes et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al (2015) reported that patients with late-life depression who had lower functional connectivity in the dorsal default mode network had better treatment outcome. Karim et al (2016) reported differences in brain activity in frontal and temporal cortices involving the anterior salience network and default mode network between remitted and non-remitted late-life depression patients. Therefore, intact executive function may indicate less severe pathology or preserved ability to respond to treatment.…”
Section: Executive Functioningmentioning
confidence: 98%